The Effect of Dihydromyricetin on the Pharmacokinetics of Fluconazole in Sprague-Dawley Rat Plasma, Based on High-Performance Liquid Chromatography–Tandem Mass Spectrometry - Liu H; Dong H; Guo L; Jin Y; Liu L (Dove Medical Press, 2023)
Hongchuan Liu,1 Huaihuai Dong,2 Liangjun Guo,3 Yongsheng Jin,2 Lihong Liu1 1Department of Pharmacy, Beijing Chaoyang Hospital, Capital Medical University, Beijing, 100020, People's Republic of China; 2School of Pharmacy, Naval Medical University, Shanghai, 200433, People's Republic of China; 3Department of Drug and Equipment, The 72st Group Army Hospital of PLA, Huzhou, 313000, People's Republic of ChinaCorrespondence: Yongsheng Jin, School of Pharmacy, Naval Medical University, No. 325 of Guohe Street, Yangpu District, Shanghai, 200433, People's Republic of China, Tel/Fax +86 21 8187 1227, Email ysjinsmmu@163.com Lihong Liu, Department of Pharmacy, Beijing Chaoyang Hospital, Capital Medical University, No. 8 of Gongti South Street, Chaoyang District, Beijing, 100020, People's Republic of China, Tel/Fax +86 10 85231786, Email hongllh@126.comBackground: The synergistic effect of dihydromyricetin (DHM) and fluconazole (FLC) can improve the killing effect of FLC-resistant Candida albicans in vitro and in vivo. However, it is not clear whether DHM affects the pharmacokinetic characteristics of FLC.Methods: In this study, 12 Sprague-Dawley (SD) rats were randomly divided into two groups as follows: (1) an FLC group in which rats were administered FLC only (42 mg/kg orally); (2) an FLC with the combined administration of DHM group, in which rats received an equivalent FLC dose immediately following the administration of DHM (100 mg/kg). Blood samples were collected from the ocular choroid vein of rats and converted into plasma. The concentrations of FLC in the rat plasma were then determined by high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS), and the related pharmacokinetic parameters were analysed. The initial mobile phase included 0.1% acetonitrile and water with gradient elution. Multiple reaction monitoring modes of m/z 307.2→ 220.1 for FLC, and m/z 237.1→ 194.2 for carbamazepine, were utilised to conduct quantitative analysis.Results: The calibration curve of FLC in rat plasma demonstrated good linearity in the range of 0.1- 30 μg/mL (r > 0.99), and the lower limit of quantification was 0.1 μg/mL. Moreover, the intra- and inter-day precision relative standard deviation of FLC was less than 9.09% and 6.51%, respectively. There were no significant differences in the pharmacokinetic parameters between the two groups.Conclusion: The results showed that DHM administration did not significantly alter FLC pharmacokinetics in SD rat plasma.Keywords: HPLC-MS/MS, dihydromyricetin, fluconazole, pharmacokinetic